2017
DOI: 10.3389/fphys.2017.00316
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Ventilatory Activity with Structured Light Plethysmography (SLP) Reduces Instrumental Observer Effect and Preserves Tidal Breathing Variability in Healthy and COPD

Abstract: The use of a mouthpiece to measure ventilatory flow with a pneumotachograph (PNT) introduces a major perturbation to breathing (“instrumental/observer effect”) and suffices to modify the respiratory behavior. Structured light plethysmography (SLP) is a non-contact method of assessment of breathing pattern during tidal breathing. Firstly, we validated the SLP measurements by comparing timing components of the ventilatory pattern obtained by SLP vs. PNT under the same condition; secondly, we compared SLP to SLP+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Structured light plethysmography (SLP) is another emerging imaging tool. SLP is a non-contact, noninvasive method to assess breathing pattern [226]. The technique is based on the stereoscopic analysis of respiratory-related distortions of a black and white chequered pattern projected on the chest wall and abdomen [226][227][228].…”
Section: Other Investigationsmentioning
confidence: 99%
“…Structured light plethysmography (SLP) is another emerging imaging tool. SLP is a non-contact, noninvasive method to assess breathing pattern [226]. The technique is based on the stereoscopic analysis of respiratory-related distortions of a black and white chequered pattern projected on the chest wall and abdomen [226][227][228].…”
Section: Other Investigationsmentioning
confidence: 99%
“…In addition, the variability of tidal breathing indices was significantly lower in patients with chronic obstructive pulmonary disease than in the healthy controls and this was further supported by similar observations from a study by Nierat et al. . The latter study also showed that, compared to using a pneumotachograph, the non‐contact SLP measurements attenuated the instrumental observer effect masking the reduced variability of tidal breathing patterns evolving in chronic obstructive pulmonary disease .…”
Section: Introductionmentioning
confidence: 77%
“…In three papers, the study groups were specifically children and one paper described a paediatric case report . Otherwise, the data for this mini review had to be drawn together from published studies and abstracts covering adults and a number of abstracts covering paediatrics .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations